1971
DOI: 10.1136/oem.28.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chrysotile and acid-treated chrysotile on macrophage cultures

Abstract: . (1971). Brit. J. industr. Med., 28, 179-185. Effects of chrysotile and acid-treated chrysotile on macrophage cultures. The addition of chrysotile asbestos to monolayer cultures of peritoneal and alveolar macrophages produces an increase in membrane permeability, as measured by eosin uptake and lactic dehydrogenase activity of the supernatant fluid. The lactate synthesis is increased, however. It is suggested that the permeability of the cell membrane is increased while dust particles are being phagocytosed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The surface of CA consists mainly of magnesium ions that are released following acid treatment, leaving a predominantly silicate surface. Increased cytotoxicity of acid-treated chrysotile compared with untreated chrysotile was observed following exposure of guinea pig macrophages to both types of asbestos (Beck et al, 1971). We also observed increased cytotoxicity of acid-treated chrysotile in human PAMs.…”
Section: Discussionsupporting
confidence: 63%
“…The surface of CA consists mainly of magnesium ions that are released following acid treatment, leaving a predominantly silicate surface. Increased cytotoxicity of acid-treated chrysotile compared with untreated chrysotile was observed following exposure of guinea pig macrophages to both types of asbestos (Beck et al, 1971). We also observed increased cytotoxicity of acid-treated chrysotile in human PAMs.…”
Section: Discussionsupporting
confidence: 63%
“…;6< # by some other inorganic dusts. Beck et al 26 have shown an increase in capillary permeability by chrysotile fibres sufficiently severe to allow red cell diapedesis through the capillary wall into the tissues, and this might explain why the distribution of fibrosis in asbestosis is similar to that seen in other types of chronic inflammatory exudates. The presence of Kerley B lymphatic lines on the chest radiograph of some patients with asbestosis2 7-as well as on those of patients with other chronic exudates-and the striking desquamative These observations pose two questions.…”
Section: Distribution Of Lung Fibrosis With Inorganic Dustsmentioning
confidence: 99%
“…Although the cellular effect of silica and asbestos dusts has been extensively studied (Allison et al, 1966;Parazzi et al, 1968;Beck et al, 1971;Harington et al, 1973;Rajan et al, 1972) little research has been conducted on the effect of talc on cells. Schnitzer and Pundsack (1970), using a red cell haemolysis test (Stalder and Stoeber, 1965) Available information on the cellular effect of mineral dusts indicates that platy talc is inactive, unlike the fibrous dusts silica and crocidolite which have significant biological activity.…”
Section: Mineralogymentioning
confidence: 99%